2022
DOI: 10.3390/ijms23169400
|View full text |Cite
|
Sign up to set email alerts
|

“Universal” Antimicrobial Combination of Bacitracin and His6-OPH with Lactonase Activity, Acting against Various Bacterial and Yeast Cells

Abstract: The effect of Bacitracin as an antibiotic acting against Gram-positive bacterial cells was evaluated in combination with hexahistidine-containing organophosphate hydrolase (His6-OPH), possessing lactonase activity against various N-acylhomoserine lactones produced by most Gram-negative bacteria as quorum-sensing molecules. The molecular docking technique was used to obtain in silico confirmation of possible interactions between molecules of His6-OPH and Bacitracin as well as the absence of a significant influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 42 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…Combination of QQ enzymes with antimicrobial agents is one of the most current and effective solutions in antimicrobial therapy. For example, it has been demonstrated that the use of YtnP lactonase in combination with antibiotics leads in an increase in its efficacy in the treatment of systemic Pseudomonas aeruginosa infections [ 31 , 49 ]. The interest in conducting this study was based on the desire of the authors to explore the possibility of combining lactoferrin-derived AMPs with lactone-hydrolyzing enzymes, His 6 -OPH and PvdQ acylase to obtain antimicrobials with improved action against various microorganisms by combining AMPs with QQ-enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combination of QQ enzymes with antimicrobial agents is one of the most current and effective solutions in antimicrobial therapy. For example, it has been demonstrated that the use of YtnP lactonase in combination with antibiotics leads in an increase in its efficacy in the treatment of systemic Pseudomonas aeruginosa infections [ 31 , 49 ]. The interest in conducting this study was based on the desire of the authors to explore the possibility of combining lactoferrin-derived AMPs with lactone-hydrolyzing enzymes, His 6 -OPH and PvdQ acylase to obtain antimicrobials with improved action against various microorganisms by combining AMPs with QQ-enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…To accumulate biomass, the cells of bacteria were aerobically cultivated in the corresponding culture medium as described previously [ 33 , 49 ]. Yeast cells were grown in the corresponding culture medium as it was described previously [ 31 ]. The bacterial and yeast cells were cultivated using a thermostatically controlled Adolf Kuhner AG shaker (Basel, Switzerland) at 28 °C for G(−) and yeasts and 30 °C for G(+), with constant stirring at 150 rpm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most appropriate practical application of His 6 -OPH, in this case, seems to be in combination with antimicrobials, which can have a major suppressive effect on microbial cells; then, the enzyme becomes a tool for weakening the resistance of cells to antimicrobial effects. Since the presence of antimicrobial agents can have a negative effect on the manifestation of enzyme activity, a significant role is currently assigned to computer methods of molecular modeling [ 4 , 6 , 46 , 60 , 61 , 62 , 63 ], including the search for the most successful partners to create effective antimicrobial combinations based on His 6 -tagged OPH [ 64 , 65 , 66 , 67 ]. At the same time, on the basis of the data obtained, as a rule, several important parameters can be estimated: the localization of molecules stabilizing the dimer of the enzyme on its surface, the possible overlap of the active cents of the enzyme, and the affinity of the interaction between the molecules of the “partners” [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ].…”
Section: His-tagged Oph Involved In the Immobilized Antimicrobial Com...mentioning
confidence: 99%
“…As it was found, various polyelectrolytes can act as such enzyme-stabilizing molecules ( Table 2 ); these molecules themselves do not possess antimicrobial properties, but they can be used in antimicrobial preparations [ 64 , 65 , 68 ]. However, the most interesting options are those when the molecules involved in the stabilization of the enzyme themselves have antimicrobial action [ 19 , 65 , 66 , 67 , 68 , 70 ]. These compounds include various so-called antimicrobial polypeptides (AMPs), which are usually of natural origin and can be synthesized by different living organisms.…”
Section: His-tagged Oph Involved In the Immobilized Antimicrobial Com...mentioning
confidence: 99%